COMPOSITION OF THE ESSENTIAL OIL FROM MIMOSA PUDICA LINN. - TK, VISMAYAVISWAN; J, DHARANI; R, SRIPATHI; S, RAVI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: To determine the composition of the essential oil obtained from Mimosa pudica L. (Mimosaceae) Methods: The essential oil of M. pudica was obtained by hydro distillation using a Clevenger apparatus and the chemical composition was determined by GC-MS analysis. Results: About 23 compounds were identified from the essential oil which constitutes about 98.92 % of the oil. Among the compounds identified phthalic acid dioctyl ester (27.76 %), α-Linolenic acid (20.34 %), Cinnamaldehyde (16.24 %) are the major compounds. α-Linolenic acid is an n-3 fatty acid. Conclusion: α-Linolenic acid is one of the essential fatty acids, which is necessary for health and cannot be produced within the human body. Mimosa pudica L. (Mimosaceae) appears to be a promising herb to undergo a wide exploration